Adapting to the new educational context: towards a theoretical-practical model for online teaching - Jordán Enamorado, Miguel Ángel; Ricart Vayá, Alicia (Revista Complutense de Educación, 2022)
The health crisis caused by Covid-19 has affected society as a whole and, consequently, the field of education. Capacity and mobility restrictions have led to the implementation of distance learning methodologies or hybrid teaching. This contemporary academic context requires a process of reflection and methodological adaptation on the part of the educational community. The aim of this paper is to offer some guidelines to contribute to the process of creating a theoretical-practical model that can work as a guide when designing methodologies and projects for online teaching. The methodology followed to this end consisted ofa literature review on the evolution of distance education pedagogy and the role of the teacher, 21st century skills, the principles of educational practice for online teaching and distance assessment. Based on this theoretical framework, we have developed our proposal, divided into three phases: the design of methodologies, teaching delivery and dealing with students in the virtual environment. Our theoretical-practical model, which has already been effectively implemented during the academic year 2020/21, contributes to the creation of a unified theoretical framework necessary to achieve an appropriate process of adaptation to the current academic context.